Cyclophilin40 isomerase activity is regulated by a temperature-dependent allosteric interaction with Hsp90. Issue 5 (19th October 2015) - Blackburn, Elizabeth A.; Wear, Martin A.; Landré, Vivian; Narayan, Vikram; Ning, Jia; Erman, Burak; Ball, Kathryn L.; Walkinshaw, Malcolm D.
Abstract : Binding the C-terminus of heat shock protein 90 (Hsp 90) to the tetratricopeptide repeat (TPR) domain of cyclophilin 40 (Cyp40) allosterically changes the dynamics of the cyclophilin-active site and reduces peptidyl-prolyl isomerase (PPIase) activity. Abstract : Cyclophilin 40 (Cyp40) comprises an N-terminal cyclophilin domain with peptidyl-prolyl isomerase (PPIase) activity and a C-terminal tetratricopeptide repeat (TPR) domain that binds to the C-terminal–EEVD sequence common to both heat shock protein 70 (Hsp70) and Hsp90. We show in the present study that binding of peptides containing the MEEVD motif reduces the PPIase activity by ∼30%. CD and fluorescence assays show that the TPR domain is less stable than the cyclophilin domain and is stabilized by peptide binding. Isothermal titration calorimetry (ITC) shows that the affinity for the–MEEVD peptide is temperature sensitive in the physiological temperature range. Results from these biophysical studies fit with the MD simulations of the apo and holo (peptide-bound) structures which show a significant reduction in root mean square (RMS) fluctuation in both TPR and cyclophilin domains when–MEEVD is bound. The MD simulations of the apo-protein also highlight strong anti-correlated motions between residues around the PPIase-active site and a band of residues running across four of the seven helices in the TPR domain. Peptide binding leads to a distortion in the shape of the active site and a significant reduction in these strongly anti-correlated motions, providing an explanation for the allosteric effect of ligand binding and loss of PPIase activity. Together the experimental and MD results suggest that on heat shock, dissociation of Cyp40 from complexes mediated by the TPR domain leads to an increased pool of free Cyp40 capable of acting as an isomerase/chaperone in conditions of cellular stress.